Faith & reason - Blocher, Henri; DiMauro, Damon (Peabody, Massachusetts : Hendrickson Publishers, 2017)
In this primer on apologetics, Henri Blocher helps readers navigate the relationship and tensions between faith and reason. "Doing apologetics" means presenting arguments to lead people to faith or to con rm them in their faith. After discussing the relationship between faith and reason, the author addresses several of the thorniest questions that trouble our efforts to unify a heart for Jesus with a mind at work: How do we combine science and faith?; Does the Bible contain errors?; Can we make the Bible say whatever we want? In discussing all of these issues in Faith and Reason, the author reminds us of the motivations that should prompt us to seek the most persuasive reasons for believing: to make our decision to have faith a responsible one, to increase our love for the people around us, and to bring glory to God. - back of book.
Includes bibliographical references.
Print version record.
Added to collection customer.56279.3
Keywords: Faith and reason -- Christianity; Apologetics; Apologetics; Faith and reason -- Christianity; RELIGION / Christian Theology / General; Electronic books